THE EFFECTIVENESS OF NATURAL ZEOLITE AS METAL ABSORBENT COPPER(II) IN POOL WATER WITH COLOUMN ADSORPTION METHOD - - Suyanta; Cerry Reggiani Catri (Jurnal Penelitian Saintek, 2016)
This study was aimed at separating copper(II)ions contained in the pool water by coloumn adsorption method. The coloumn was ﬁ lled up with natural zeolite taken from Gunungkidul. The inﬂ uence of zeolite size in particular contact time toward the effectiveness of the zeolite to adsorb metal ions of copper (II) ions were studied in this research. The effectiveness of zeolite adsorption was based on the efﬁ ciency value which is the ratio between the concentration of metal ions of copper (II) adsorbed by the metal ion concentration of copper (II) prior to adsorption. Copper metal ion concentrations were determined using Atomic Absorption Spectroscopy (AAS). The results show that the ability of the column adsorption system in the separation of metal ions of copper (II) was quite high. Column with zeolite 1 (size 10 mesh) can lower copper consentration up to 37.1698%, while the zeolite column 2 (size 5 mesh) can lower the consentration up to 35.9976%. These results indicate that the copper ions in the pool water can be separated quite well.